2018
DOI: 10.18632/oncotarget.25421
|View full text |Cite
|
Sign up to set email alerts
|

Deferasirox, an oral iron chelator, with gemcitabine synergistically inhibits pancreatic cancer cell growthin vitroandin vivo

Abstract: ObjectivesIron is an essential element for cell proliferation and growth processes. We have reported that deferasirox (DFX), an oral iron chelator, showed antiproliferative activity against pancreatic cancer cells. This study aimed to elucidate the effects of combination of gemcitabine (GEM), standard chemotherapy for pancreatic cancer, and DFX in vitro and in vivo.ResultsGEM+DFX showed antiproliferative activity and induced apoptosis in pancreatic cancer cells in vitro. GEM+DFX suppressed xenograft tumor grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Much is still unknown regarding the mechanism of action of iron chelators. We have investigated the ability of DFX ability to suppress tumour proliferation, and found that it suppresses proliferation in a concentration-dependent manner [10], it improves sensitivity to GEM [11], and that the combination of DFX and sorafenib is better than DFX alone at suppressing liver cancer [12]; we have also examined other secondary effects of iron chelators. Upon conducting a supplementary microarray analysis of the in vivo samples used [10], we observed that the expression of Rho-family genes like Rac1 and Cdc42, involved in cellular movement pathways, was altered in DFX-treated cells, and have begun to consider the possibility that DFX could reduce the metastatic and invasive capabilities of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Much is still unknown regarding the mechanism of action of iron chelators. We have investigated the ability of DFX ability to suppress tumour proliferation, and found that it suppresses proliferation in a concentration-dependent manner [10], it improves sensitivity to GEM [11], and that the combination of DFX and sorafenib is better than DFX alone at suppressing liver cancer [12]; we have also examined other secondary effects of iron chelators. Upon conducting a supplementary microarray analysis of the in vivo samples used [10], we observed that the expression of Rho-family genes like Rac1 and Cdc42, involved in cellular movement pathways, was altered in DFX-treated cells, and have begun to consider the possibility that DFX could reduce the metastatic and invasive capabilities of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in breast cancer patient-derived xenograft models, it has been reported that tumor recurrences are delayed by the combination without enhancing the side-effects of chemotherapies or impairing systematic iron homeostasis of the mice [182,183]. DFX can also synergistically repress pancreatic cancer cell proliferation with gemcitabine, a standard chemotherapy for pancreatic cancer, in vitro and in vivo [184].…”
Section: Iron Manipulating Strategies In Cancermentioning
confidence: 99%
“…Chelators are frequently used in combination with other therapies. As an example, DFO was associated with many different chemotherapeutic drugs such as cyclophosphamide, thiotepa, etoposide, carboplatin and cisplatin [121][122][123]. However, some cancers are resistant to Fe-chelators, probably because of their low membrane permeability properties [119].…”
Section: Fe Chelatorsmentioning
confidence: 99%